Modification of montmorillonite with a cationic softener for finishing cotton fabric with hand builder performance - Kittinaovarat, Siriwan; Jiratumnukul, Nantana; Koolpreechanan, Narissara (Journal of Metals, Materials and Minerals, 2011)
Montmorillonite (Mont) was modified by cationic exchange with the cationic softener TEGO 28 (Di-Palm carboxyethyl hydroxyethyl methyl ammonium methosulfate). XRD analysis suggested that intercalation occurred in the modified Mont (mMont). Softening finishing solutions composed of pure TEGO 28 with and without mMont were treated on cotton fabrics by the pad-dry method and then evaluated for stiffness, whiteness, tear strength and thermal stability. TEGO 28 treatment alone increased the stiffness property of the finished fabrics, and this was increased further by the co-inclusion of mMont at 3 and 5% (w/v), but higher or lower mMont concentrations led to a marked and slight, respectively, reduction in stiffness, especially at 15% (w/v) mMont. The degree of whiteness of the finished fabrics decreased slightly with the addition of TEGO 28 alone and was further slightly decreased in a dose-dependent manner with the co-addition of increasing concentrations of mMont. In contrast, the tear strength and thermal stability of the finished fabrics both increased with increasing concentrations of mMont in the softening finishing solution.